First Cenomanian record of insects in the Southern Hemisphere, with Perforissidae (Fulgoroidea) and Cupedidae (Coleoptera) from Southern Patagonia, Argentina - Petrulevicius, Julian Fernando (2014)
The discovery of the southernmost world record (49.5S) of a Late Cretaceous insect fauna and plant-insect interactions is reported herein. The new locality is from the middle Cenomanian lacustrine deposits of the Mata Amarilla Formation belonging to the Austral foreland Basin, southwest Patagonia, Argentina. A first trip to the locality yielded few specimens of Coleoptera, among them an Archostemata: Cupedidae, and also a tiny specimen of Fulgoroidea: Perforissidae represented by Aonikenkissus zamunerae gen. et sp. nov. The Perforissidae were previously recorded from the Berriasian (?)-Barremian, Aptian, Albian, Turonian and Santonian in the Northern Hemisphere. The new species represents the first record of Perforissidae for South America and for the whole Southern Hemisphere. The new record suggests that the Perforissidae had a broader biogeographical distribution, and seem to have been cosmopolitan in the mid-Cretaceous. The Cupedidae reported herein is the first record for the Cenomanian and the first record of the genus Zygadenia in South America. Insect traces found in the same strata are made in an angiosperm palmatilobed leaf and correspond to a piercing and sucking type of damage. This type of damage is compared to recent stipples and to isolated piercings.